Controllable synthesis of CO2‐based poly(carbonate‐ether)diols catalyzed by Salen–cobalt complex. Issue 17 (27th May 2022) - Fan, Chaogang; Lu, Shujuan; Ge, Qingyun; Lin, Shaohui; Pan, Qinmin
Abstract: In our research, the terpolymerization of CO2 and epoxides was realized and the poly(carbonate‐ether)diols were successfully synthesized by the catalysis of Salen–metal complex with the non‐nucleophilic anion, in which the alternated polycarbonate is generally produced. The poly(carbonate‐ether)diols with M n s between 1100 and 8100 g mol −1 and carbonate units (CU) between 31.3% and 52.9% were obtained by tuning temperature, CO2 pressure, time and water addition. Especially the oligo(carbonate‐ether)diols with M n s below 2000 g mol −1 and CU over 40% could be obtained, which were ideal starting materials for polyurethane synthesis and novel CO2 ‐based polymers with high potential. Abstract :